EFEKTIVITAS PEMBERIAN TAMBAHAN PENGHASILAN PEGAWAI (TPP) TERHADAP KINERJA PEGAWAI - Thahir, Muhammad Ardhyan; Wahid, Nur; Ma'ruf, Adnan (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2024)
The aim of this research is to describe the effectiveness of employee performance at the West Sinjai District Office from the aspects of work quantity, work quality and time utilization. This type of research uses qualitative research methods. The data collection techniques used were observation, direct documentation interviews in the field, the informants in this study consisted of 3 people. The results of this research show that in terms of the performance indicators used, they include: (1) the quantity of work after providing additional income, employees are more active in providing information to the public (2) the quality of work of West Sinjai District office employees is seen from the perspective of knowledge regarding their duties and obligations in accordance with each employee is able to understand their field. Even the targets or results are as expected (3) utilization of time Looking at the results of the interview above, it appears that there are still employees who lack discipline even though employees have been given additional employee income as additional income in the hope that employees can work optimally and optimally in carrying out their duties.